Applied multiplex allele specific PCR to detect second-line drug resistance among multidrug-resistant tuberculosis in China. (December 2017) - Liang, Ya-ping; Chen, Yan; Xiao, Tong-yang; Xia, Qiang; Liu, Hai-can; Zhao, Xiu-qin; Zeng, Chun-yan; Zhao, Li-li; Wan, Kang-lin
Abstract: Rapid detection of resistance to the second-line drugs is essential for early initiation of appropriate anti-tubercular treatment regimen among multi-drug tuberculosis (MDR-TB). In this study, we applied a multiplex allele-specific PCR (MAS-PCR) to identify the mutations on codons 90 and 94 of gyrA and nucleotide 1401 of rrs for detecting ofloxacin (OFX) and kanamycin (KAN) resistance in 139 MDR-TB isolates from China. Using the traditional phenotypic method as the reference, MAS-PCR detected resistance to OFX and KAN with sensitivities of 67.3% and 76.5%, respectively, and specificities of 100.0%. Therefore, MAS-PCR assays can be used for rapid detection of second-line drug resistance among MDR-TB in China, enabling early administration of appropriate treatment regimens to the affected MDR-TB patients.